(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
The objective of our study is to analyse the variation in terms of age, sex, month, time before death, type of injury externally, type of material caused electrocution, place of incident, occupation and cause of deathof the various cases of electrocution deaths in Patiala region. Data is analysed retrospectively over a period of seven years from April 2005 to March 2012 of the cases came for post mortem examination in our department. Study revealed that majority of victims were male (91.11%) and age range was 3 to 70 years with average of 35.58 years with maximum number of cases in age group of 31-40 years (22.22%). There is increase in number of cases in summer season (55.55%) andmost of the cases are found in farms (48.88%)followed by at home (26.66%). In most of cases electrocution was from wires (55.55%) and switches (15.55%). It was found that 66.67% of deaths are within first hour of electric shock. In most of cases current involved is low voltage (74%) and cause of death mostly cardiac failure (55.55%).